PENGARUH PENATAUSAHAAN DAN PENERAPAN SISTEM INFORMASI MANAJEMEN AKUNTANSI BARANG MILIK NEGARA (SIMAK BMN) TERHADAP KUALITAS LAPORAN KEUANGAN (STUDI KASUS PADA SATUAN KERJA PERGURUAN TINGGI NEGERI WILAYAH YOGYAKARTA) - Agus Santosa; Aditya Kurniawardana; Gita Astyka Rahmanda (Develop, 2023)
Abstract: The Effect of Administration and Application of State Property Accounting Management Information System (SIMAK BMN) on the Quality of Financial Reports (Case Study in the Work Unit of State Universities in Yogyakarta Region). The purpose of this research is to analyze the effect of administration and application SIMAK BMN on the quality of financial reports in work units of state universities, either simultaneously or partially. The research was conducted in 3 PTN (2 BLU 1 work unit) as Kemendikbudristek entities, by used primary data (questionnaires), secondary data from 2018 to 2021 Audited Financial Reports at State Universities in the Yogyakarta area. The sample in this research were 45 employees of asset accounting and financial accounting from 3 PTN. This research used multiple linear regression analysis model with SPSS 23 software with independent variables are bookkeeping, inventory, reporting, application of SIMAK BMN, and the dependent variable is the quality of financial reports. The results of the research prove that bookkeeping, inventory, reporting, and the application of SIMAK BMN simultaneously affect to the quality of financial reports. Partially it was found that bookkeeping, inventory, reporting, and application of SIMAK BMN had a significant positive effect to the quality of financial reports.` Keywords: Bookeeping, Inventory, Reporting, Application of SIMAK-BMN, Quality of Financial Reports.